2018
DOI: 10.1111/jog.13770
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of monocyte subsets and polarization in preeclampsia and intrauterine fetal growth restriction

Abstract: These results show for the first time, a shift towards increased intermediate maternal monocyte subtype in IUGR and in preterm PE as well as skewing of maternal peripheral monocytes (all subsets) towards M2 phenotype in pregnancies complicated by IUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…While Flt-1 weakly correlated with CD163, the findings are consistent with Flt-1 related M1 upregulation of macrophages demonstrated in preeclamptic decidua [40] and may reflect monocyte activity such as chemotaxis. The inflammatory intermediate monocyte subset has been shown to be increased in preterm preeclampsia and fetal growth restriction as well as term pregnancy [34]. The current study findings of a gestational increase in Flt-1 and endoglin as well as with M1 polarization may represent an increase in the Flt-1 and endoglin expression by more inflammatory monocytes.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…While Flt-1 weakly correlated with CD163, the findings are consistent with Flt-1 related M1 upregulation of macrophages demonstrated in preeclamptic decidua [40] and may reflect monocyte activity such as chemotaxis. The inflammatory intermediate monocyte subset has been shown to be increased in preterm preeclampsia and fetal growth restriction as well as term pregnancy [34]. The current study findings of a gestational increase in Flt-1 and endoglin as well as with M1 polarization may represent an increase in the Flt-1 and endoglin expression by more inflammatory monocytes.…”
Section: Discussionsupporting
confidence: 49%
“…CD86 is a cell surface protein strongly expressed by M1-type macrophages / monocytes [[31], [32], [33]]. The monocyte expression of anti-inflammatory molecule, CD163 and the CD86/CD163 ratio can be used as a marker of M1 and M2 phenotypes [34]. M2 polarized macrophages play a role in resolution of inflammation, accompanied by reduced pro-inflammatory cytokine secretion [35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations confirm the previous findings on its relevance. In recent work of Alahakoon and colleagues, the authors estimated quantities of classical, intermediate and non-classical monocytes in blood samples from preeclamptic patients (with or without intrauterine growth restriction, IUGR) and uncomplicated pregnancies [92]. The authors observed a significantly lower content of classical monocytes for both PE groups (with or without IUGR), while the number of inflammatory monocytes which combined intermediate and non-classical subsets for these groups was significantly increased as compared with the control.…”
Section: Monocyte–macrophage System During Pregnancymentioning
confidence: 99%
“…Immunological dysfunction: There is clear evidence that the immune system in women with an IUGR pregnancy differs compared to those without IUGR (190). This study found that peripheral monocytes in women with an IUGR pregnancy had a more classically anti-inflammatory profile than monocytes from women with an uncompromised pregnancy.…”
Section: Overcoming the Hurdles To Progressmentioning
confidence: 99%